Management of Ophthalmopathy and Use of Selenium in Graves' Disease: A Survey of Physicians from the Middle East and Africa - Beshyah, Salem A.; Khalil, Aly B.; Bashir, Mohammed (Journal of Diabetes and Endocrine Practice, 2025)
Objectives We explored how physicians in the Middle East and Africa (MEA) assess and manage Graves' ophthalmopathy (GO) and ascertain their perceptions of selenium (Se) in thyroid disease.Methods Two online questionnaires were sent to a sample of physicians from the MEA region. Responses from 183 GO and 102 Se surveys were received and analyzed.Results In the GO survey, 68.6% thought multidisciplinary team (MDT) was very valuable, but fewer participated in MDT (19.0%) or referred patients to MDT (44.2%). Respondents advocated the assessment of visual fields by perimetry (65.9%), magnetic resonance imaging (52.9%), color vision (51.8%), and ultrasonography (14.1%). Autoimmune thyroid diseases (ATDs) were the most common choice (95.1%) for first-line therapy for coexisting hyperthyroidism. Glucocorticoids (GCs) were preferred as the first-line therapy by the majority of respondents; among them, 63.1% chose the intravenous route. The treatment strategy for GO with intravenous GC therapy remains debatable and surgical decompression (31.3%) and radiotherapy (13.1%) were recommended. When diabetes coexists, radiotherapy and orbital decompression are more favored over GCs. Regarding the Se survey, a minority (10.3%) used Se routinely for Graves' disease (GD). However, this increased to 29.1% when GO exists. However, about a quarter needed to be sure/did not know (23.9%) the evidence in GD without GO and 27.4% for GD with GO. In GD without GO on ATDs, 67.5% never recommend Se, whereas 32.5% recommend Se sometimes. Conversely, when GO occurs, 65.0% recommend Se in variable frequencies. Of these, Se is used as an alternative to watchful waiting in patients with mild ocular involvement (22.1%) and as an adjuvant to the established treatment in patients with moderate to severe ocular involvement (20.4%). The dose of 200 mcg/day was recommended by 42.5% of respondents.Conclusion Gaps exist in the physicians' knowledge and practices concerning diagnosis and management of GO. More focused education and training are needed in the MEA region.
Keywords: clinical management; Graves' ophthalmopathy; Graves' disease; selenium; thyroid eye disease; thyrotoxicosis